2007
DOI: 10.1021/ma070046d
|View full text |Cite
|
Sign up to set email alerts
|

Defunctionalization of Ester-Substituted Electrochromic Dioxythiophene Polymers

Abstract: This work demonstrates a simple process to form insoluble poly(3,4-propylenedioxythiophene) (Poly[ProDOT]) films by defunctionalization of a soluble form, which is useful in the fabrication of multilayer polymer devices. Three new ester disubstituted Poly[ProDOTs], soluble in common organic solvents, including chloroform, methylene chloride, toluene, tetrahydrofuran, and ethyl acetate, have been synthesized by oxidative polymerization using iron(III) chloride. These Poly[ProDOT-diesters] have the expected repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
87
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 23 publications
3
87
2
Order By: Relevance
“…11,35 The solubility of the polymer can be adjusted by using labile groups as well. 41 However, the removal of the labile group is usually very tedious.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,35 The solubility of the polymer can be adjusted by using labile groups as well. 41 However, the removal of the labile group is usually very tedious.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 Reeves et al reported a novel way to process ProDOT-based polymers using defunctionalization route. 11 They used a soluble polymer which can be converted into an insoluble polymer via chemical modification of the pendant side chain.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers that can be solution-processed and, subsequently, defunctionalized to produce films insoluble in most conventional organic solvents have recently emerged for use in EC and multilayer light-emitting diode (LED) devices, [38] transistors, [39] and photovoltaic cells. [40] In the case of P4c, we found that the spray-cast polymer can be effectively defunctionalized by immersing the films in a 1 M KOH methanol solution for 4 h at 70 8C.…”
mentioning
confidence: 99%